Mooring Chain Fatigue Analysis at the Single Point Mooring Ardjuna Marine Terminal Due to the Combination of Wave, Current, and Wind Loads Using the Fracture Mechanics Method - Rafi Manaf Mawardi; Daniel Mohammad Rosyid; Rudi Walujo Prastianto; Raditya Danu Riyanto (International Journal of Offshore and Coastal Engineering, 2026)
Mooring chain failure in Single Point Mooring (SPM) systems is a critical risk in offshore operations due to cyclic and complex environmental loading. The combination of waves, currents, and winds produces stress fluctuations that trigger crack initiation and propagation that can potentially lead to structural failure. This study analyzes the fatigue behavior of mooring chains in SPM at Ardjuna Marine Terminal, Java Sea, using a fracture mechanics approach. Cracks are modeled as semi-elliptical surface cracks, and the crack propagation rate is predicted using Paris Law based on Stress Intensity Factor (SIF) evaluation through numerical simulations. The motion responses of SPM and FSO are analyzed using Executive software, while the mooring chain stress analysis is performed using Dynamic simulation software. The results show a maximum SIF value of 1821.8 MPa√mm with a deviation of 1.6% from the analytical solution. The crack propagation rate increases from 2.65×10⁻⁸ to 3.02×10⁻⁵ mm/cycle, resulting in a total fatigue life of 8.3 years. These findings emphasize the importance of fracture mechanics-based evaluation to support inspection and maintenance strategies for SPM mooring systems.